MODERN TRENDS OF MANAGEMENT IN TRANSPORT - Lejskova, Pavla (Doprava a spoje, 2005)
Specificity of management in Czech transport is influenced by globalization of the world economy and its discontinuous development of turbulent market environment, to which transport companies accommodate very hardly, current development of European transport policy and legislative with integrative trends and transport interoperability and intermodal requirements and requirement of economic and social cohesion of EU countries.